El Dr. Bermejo, amable ciceron del Cr. Mabry - Davila Garcia, Carmen Rosa (Revista Universidad de Guayaquil, 1998)
We had the opportunity to interview Mr. Mabry on TV alongside Dr. Bermejo, who was collaborating with him, exchanging scientific points of view. In that interview, we talked about the different research projects and how natural products are used in the US, and we learned that they are focused on DNA studies there, and that Europe is the great defender of natural products. Dr. Bermejo asked him about Taxol, a product isolated from the bark of the Pacific yew (*Taxus brevifolia*), the most important and useful antitumor agent discovered in recent decades. Dr. Bermejo pointed out that, unfortunately, the content of this substance in the bark is very low and not very soluble in the carrier agents generally used in injections, which is why other researchers in France looked for another variety of yew (*Taxus baccata*).